Correction: Revealing the electronic, optical and photocatalytic properties of PN-M2CO2 (P = Al, Ga; M = Ti, Zr, Hf) heterostructures. Issue 6 (6th March 2023) - Munawar, M.; Idrees, M.; Alrebdi, Tahani A.; Amin, B.
Abstract : Correction for 'Revealing the electronic, optical and photocatalytic properties of PN-M2 CO2 (P = Al, Ga; M = Ti, Zr, Hf) heterostructures' by M. Munawar et al., Nanoscale Adv., 2023, ; https://doi.org/10.1039/d3na00017f .